2022
DOI: 10.1002/ehf2.13787
|View full text |Cite
|
Sign up to set email alerts
|

Soluble neprilysin and survival in critically ill patients

Abstract: Background Critically ill patients admitted to an intensive care unit (ICU) exhibit a high mortality rate irrespective of the initial cause of hospitalization. Neprilysin, a neutral endopeptidase degrading an array of vasoactive peptides became a drug target within the treatment of heart failure with reduced ejection fraction. The aim of this study was to analyse whether circulating levels of neprilysin at ICU admission are associated with 30 day mortality. Methods and resultsIn this single-centre prospective … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…In addition, as a neprilysin inhibitor, sacubitril can effectively reduce the circulating levels of neprilysin. A previous study suggested that higher levels of circulating neprilysin in critically ill patients were not associated with 30‐day mortality [30].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, as a neprilysin inhibitor, sacubitril can effectively reduce the circulating levels of neprilysin. A previous study suggested that higher levels of circulating neprilysin in critically ill patients were not associated with 30‐day mortality [30].…”
Section: Discussionmentioning
confidence: 99%
“…However, the exact mechanism of action of these drugs remains largely unclear. Interestingly, circulating angiotensin II (Ang II) and neprilysin are increased during sepsis [28][29][30]. The potential effects of SV on sepsis-induced ALI have not yet been reported.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, it is worth noting that NEP cleaves angiotensin II into angiotensin-(1–4) and angiotensin-(5–8) and could theoretically by-pass ACE by directly generating angiotensin-(1–7) from angiotensin I. Although the circulating concentration of NEP is increased in critically ill patients [ 55 ], such increase is not associated with prognosis, potentially because concentration and activity are dissociated during septic shock, likely due to endogenous inhibitors [ 56 , 57 ].
Fig.
…”
Section: Introductionmentioning
confidence: 99%